Penentuan dan Pengendalian Ruang Simpan Pendingin dan Hubungannya dengan Stok Pada Industri Makanan - Agung Chandra (Jurnal METRIS, 2014)
factors: unit of measurement, storage dimension, packaging dimension, minimum and maximum stock, andaisle allowance. Unit of measurement is used to convert inventory stock to physical inventory. Dimension isused to determine space area and stacks, include effective storage area and utilization. Minimum andmaximum stock are used as indicator for monitoring current stock and to predict space area that will be usedfor some periods ahead. Aisle allowance is used for material and personnel movement. Next research needsto be developed for layout model to get the whole view of storage area.